AN OVERVIEW OF THE NUTRITIONAL STATUS OF CHILDREN AGED 6 - 60 MONTHS AT "KHANZA DAYCARE" - Jannah, Jauharotul (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Nutritional problems are one of the most common health problems, especially among children in the world. Malnutrition will cause stunted growth and development of children. Nutritional status is the sensitive indicator of a child's health, and under-five children constitute the most vulnerable segment of any community. Adequate nutrition is a necessary first step in the improvement of quality of life. Nutrition plays a key role in the physical, mental, and emotional development of children, and much emphasis has been given to provide good nutrition to growing populations, especially in the formative years of life. Aims: To overview of the nutritional status of children aged 6 60 months at Khanza Daycare. Methods: This type of research is descriptive research with a cross sectional approach. Sampling was carried out using total sampling technique. The research population was children aged 6 36 months with a sample size of 12 children. Results: The research results showed that the child had a normal weight of 100. Short children 16.7, normal 83.3. Children with over nutrition are 8.3 and normal nutrition are 91.7. Children at risk of overnutrition are 8.3, overnutrition 8.3, and normal 83.4. Conclusion: Based on the research results obtained, the nutritional status of children aged 6 - 60 months at Khanza Daycare has a good nutritional level, so working mothers do not need to worry about entrusting their children to the daycare.